Dolichol-phosphate mannose synthase: Structure, function and regulation - Maeda, Yusuke; Kinoshita, Taroh (Biochimica et biophysica acta, 2008)
Glycosylation is the major modification of proteins, and alters their structures, functions and localizations. Glycosylation of secretory and surface proteins takes place in the endoplasmic reticulum and Golgi apparatus in eukaryotic cells and is classified into four modification pathways, namely N- and O-linked glycosylations, glycosylphosphatidylinositol (GPI)-anchor and C-mannosylation. These modifications are accomplished by sequential addition of single monosaccharides (O-linked glycosylation and C-mannosylation) or en bloc transfer of lipid-linked oligosaccharides (N-linked glycosylation and GPI) onto the proteins. The glycosyltransferases involved in these glycosylations are categorized into two classes based on the type of sugar donor, namely nucleotide-sugars and dolichol-phosphate-sugars, in which the sugar moiety is mannose or glucose. The sugar transfer from dolichol-phosphate-sugars occurs exclusively on the luminal side of the endoplasmic reticulum and is utilized in all four glycosylation pathways. In this review, we focus on the biosynthesis of dolichol-phosphate-mannose, and particularly on the mammalian enzyme complex involved in the reaction.